THE ROLE OF CENTRAL AND REGIONAL GOVERNMENTS IN THE RESOLUTION OF LAND PROBLEMS OF THE INDONESIAN NAVY AS A MILITARY TRAINING AREA IN GRATI PASURUAN - Uciek Darmayani; Rr. Lilik Ekowati; Viv Djanat Prasita (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
ABSTRACT The Indonesian Navy owns land assets of State Property (BMN) in Grati, Pasuruan Regency covering an area of ​​36,763,350 m2 (3,676.34 Ha). In accordance with Government Regulation of the Republic of Indonesia Number 68 of 2014 concerning State Defense Territory Arrangement. There are 1,033 locations of Indonesian Forces lands that are included in the Territory The defense consists of the Indonesian Army as many as 583 locations, the Indonesian Navy as many as 93 locations and the Indonesian Air Force in 357 locations. The Defense Area consists of military bases or soldiers, military training areas, military installations, equipment testing areas, storage areas for other explosive and dangerous goods, areas for disposal of ammunition and other dangerous defense equipment, strategic national vital objects and air defense interests. the land of the Indonesian Navy BMN in Grati, Pasuruan Regency cannot be used optimally for the Indonesian Forces training area because many residents inhabit the Indonesian Navy land for agricultural land and housing so that the participation of the central and regional governments is needed in resolving these problems so that the Indonesian Navy can use the land as a training area in accordance with the Main Duties and Main Functions of the Indonesian Navy. And This research used descriptive qualitative methods and analysis is carried out based on the findings of the data that has been collected. Keywords: Policy evaluation, military training area, community relocation, team formation combined